"Engaging with birth stories in pregnancy: a hermeneutic phenomenological study of women's experiences across two generations" - Lesley Kay; Soo Downe; Gill Thomson; Kenny Finlayson (BMC, 2017)
Abstract Background The birth story has been widely understood as a crucial source of knowledge about childbirth. What has not been reported is the effect that birth stories may have on primigravid women's understandings of birth. Findings are presented from a qualitative study exploring how two generations of women came to understand birth in the milieu of other's stories. The prior assumption was that birth stories must surely have a positive or negative influence on listeners, steering them towards either medical or midwifery-led models of care. Methods A Heideggerian hermeneutic phenomenological approach was used. Twenty UK participants were purposively selected and interviewed. Findings from the initial sample of 10 women who were pregnant in 2012 indicated that virtual media was a primary source of birth stories. This led to recruitment of a second sample of 10 women who gave birth in the 1970s-1980s, to determine whether they were more able to translate information into knowledge via stories told through personal contact and not through virtual technologies. Results Findings revealed the experience of 'being-in-the-world' of birth and of stories in that world. From a Heideggerian perspective, the birth story was constructed through 'idle talk' (the taken for granted assumptions of things, which come into being through language). Both oral stories and those told through technology were described as the 'modern birth story'. The first theme 'Stories are difficult like that', examines the birth story as problematic and considers how stories shape meaning. The second 'It's a generational thing', considers how women from two generations came to understand what their experience might be. The third 'Birth in the twilight of certainty,' examines women's experience of Being in a system of birth as constructed, portrayed and sustained in the stories being shared. Conclusions The women pregnant in 2012 framed their expectations in the language of choice, whilst the women who birthed in the 1970s-1980s framed their experience in the language of safety. For both, however, the world of birth was the same; saturated with, and only legitimised by the birth of a healthy baby. Rather than creating meaningful understanding, the 'idle talk' of birth made both cohorts fearful of leaving the relative comfort of the 'system', and of claiming an alternative birth.